H.E.S.S. observations of the globular clusters NGC 6388 and M15 and search for a dark matter signal - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astrophysical Journal, 2011)
Observations of the globular clusters (GCs) NGC 6388 and M15 were carried out by the High Energy Stereoscopic System array of Cherenkov telescopes for a live time of 27.2 and 15.2 hr, respectively. No gamma-ray signal is found at the nominal target position of NGC 6388 and M15. In the primordial formation scenario, GCs are formed in a dark matter (DM) halo and DM could still be present in the baryon-dominated environment of GCs. This opens the possibility of observing a DM self-annihilation signal. The DM content of the GCs NGC 6388 and M15 is modeled taking into account the astrophysical processes that can be expected to influence the DM distribution during the evolution of the GC: the adiabatic contraction of DM by baryons, the adiabatic growth of a black hole in the DM halo, and the kinetic heating of DM by stars. Ninety-five percent confidence level exclusion limits on the DM particle velocity-weighted annihilation cross section are derived for these DM halos. In the TeV range, the limits on the velocity-weighted annihilation cross section are derived at the 10 cm s level and a few 10 cm s for NGC 6388 and M15, respectively. © 2011. The American Astronomical Society. All rights reserved..
Keywords: black hole physics; dark matter; gamma rays: general; globular clusters: individual (NGC 6388; M15)